Produksi Gas Buangan Ternak Babi yang Diumbar di Gaya Baru dan Sekitar Pasar Wosi, Manokwari - Odiktur Marani; Budi Santoso; Freddy Pattiselanno (Dinamika Lingkungan Indonesia, 2023)
The research aims to estimate the manure production and calculate the methane gas produced by the pig free-ranging system in Gaya Baru and the surrounding of Wosi Market in Manokwari. This research is conducted from May to June 2018. The methods used in this study are observation, interviews, and literature study. Direct observations in the field are carried out by calculating the pig population and estimating the body weight by measuring body length and chest circumference according to the Winter formula. Furthermore, the calculation of the amount of fresh dung (KTS) of pigs is carried out. The parameter observed in this research is the methane gas produced by the systems. Research is conducted by observation, interview, and literature review with a descriptive statistical approach. The free-ranging pig systems in Gaya Baru and its surroundings produce ammonia at 0.246617 ppm/day, biogas of 10.95m3/year, equivalent to 3996.75m3 per year, and methane of 10.85 m³ per day, or equivalent to 130.18 m³ per year. If this condition is allowed to continue, this will have a social impact, but also environmental and health problems around the research sites.